2005
DOI: 10.1590/s1806-83242005000100009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cigarette smoke inhalation on bone density: a radiographic study in rats

Abstract: ABSTRACT:The aim of this study was to evaluate the influence of cigarette smoke inhalation (CSI) and its cessation on tibiae bone quality. Forty-one male Wistar rats were randomly assigned to one of the following groups: Group 1 -control (n = 14), Group 2 -3 months of CSI and 2 months without exposure to CSI (n = 12), and Group 3 -5 months of CSI (n = 15). At the end of the experimental period, the animals were sacrificed, the tibiae removed and immediately radiographed for photodensitometric analysis. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
5
16
0
Order By: Relevance
“…The measurements performed in the groups of rats exposed to cigarette smoke alone confirmed previous findings that relatively high exposure to cigarette smoke affected the BMD of the femur in rats [22,23]. We demonstrated that the BMD of the distal end and diaphysis of the femur was lower in 4-month smoke-exposed rats than in controls.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The measurements performed in the groups of rats exposed to cigarette smoke alone confirmed previous findings that relatively high exposure to cigarette smoke affected the BMD of the femur in rats [22,23]. We demonstrated that the BMD of the distal end and diaphysis of the femur was lower in 4-month smoke-exposed rats than in controls.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the beneficial EPF effect on bone turnover during exposure to smoke consisted of stimulating the osteoblastic activity and inhibiting the smoke-stimulated bone resorption. Taking into account the observations made in the present study and the previous reports [22][23][24][25][26][27][28][29][30][31][32][33][34], the protective action of EPF on the skeleton might result from its direct action. This mechanism involved inhibition of bone resorption and stimulation of its formation through a direct influence on both the differentiation and activity of osteoblastic and osteoclastic bone cells.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Yet, Cesar-Neto et al 15 , led a radiograph study in 41 male rats Wistar, evaluating the influence in inhalation of cigarette smoke and the effect of its interruption in the tibia bone quality. The results showed that the continuous exposure to cigarette smoke promoted a significant reduction in bone density and the interruption of inhalation seems to reverse this negative effect.…”
Section: Discussionmentioning
confidence: 99%